The day the crayons quit - Daywalt, Drew.; Jeffers, Oliver (New York, NY : Philomel Books, 2013)
When Duncan arrives at school one morning, he finds a stack of letters, one from each of his crayons, complaining about how he uses them.
Keywords: Crayons -- Fiction; Letters -- Fiction; Color -- Fiction; Crayons -- Juvenile fiction; Letters -- Juvenile fiction; Color -- Juvenile fiction; Picture books for children; Epistolary fiction